IMPLEMENTASI CHROMOTHERAPY DENGAN TEKNIK SELF MANAGEMENT DALAM MENURUNKAN STRES AKADEMIK SISWA BIMBEL WW EDU DI KABUPATEN PASURUAN (Jurnal Bimbingan dan Konseling Islam, 2019)
The purpose of this study is to reveal the effect of Chromotherapy and Self Management Techniques in reducing student’s academic stress. The researcher used quantitative research method with experimental research types Pre-Experimental Design (non-design), especially One Group Pretest-Posttest. The researcher wants to see the difference between the test results before and after giving treatment to the research object. The results of this study show that count is higher than t¬table, it is 11.716>2.042. However, the results of the Sig value are higher than 0.05, it is 0.000>0.05. Thus, Ha is accepted and Ho is rejected. This means that there is a decrease in student academic stress after being given Chromotherapy and Self Management treatment.